Pengaruh Profitabilitas, Leverage , Ukuran Perusahaan dan Dewan Komisaris Independen terhadap Pengungkapan Sustainability Report - Siska Liana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
This study aims to empirically examine the effect of profitability, leverage, firm size, and independent board of commissioners on sustainability report disclosures in mining companies listed on the Indonesia Stock Exchange) for the period 2011-2015. The population of this research is that there are 41 mining companies listed on the Indonesia Stock Exchange. The method of selecting samples in this study is based on purposive sampling with predetermined criteria. In this case, the samples studied were 7 companies. The data analysis technique used is descriptive verification method which consists: classical assumptions, multiple linear regression, correlation, a coefficient of determination, T-test, and F test. The results of this study indicate that profitability and leverage have a significant effect on sustainability report disclosure, but for company size and independent board of commissioners it does not affect the disclosure of sustainability report. The results of this study are expected to be used as guidelines, both by the management of the company by looking at the impact of sustainability report disclosures, for potential investors to see differences in financial conditions and positions that make sustainability reports so that investment can be decided appropriately and for lenders to provide an indication of the level of security of the company in fulfilling its obligations.